NEXTGEN: A serious game showcasing circular economy in the urban water cycle. (10th March 2023) - Khoury, Mehdi; Evans, Barry; Chen, Otto; Chen, Albert S.; Vamvakeridou-Lyroudia, Lydia; Savic, Dragan A.; Djordjevic, Slobodan; Bouziotas, Dimitrios; Makropoulos, Christos; Mustafee, Navonil
Abstract: Understanding the Circular Economy for water is challenging. It requires being acquainted with the individual components involved in the urban water cycle such as stormwater, water conveyance, groundwater, water drainage, wastewater treatment and discharge. In addition, to appreciate benefits and tradeoffs in the context of Circular Economy, one also needs to factor the interrelations between water and other factors such as material recovery, energy use, expenses, and environmental impacts. On top of it, the fact that each catchment has a different geography, hydrology and urban setup can lead to difficulties in transferring gathered knowledge to other situations. In response to this challenge of developing a holistic understanding of applying Circular Economy to the urban water cycle, the NextGen Serious Game has been created. It is a simulation based online educational tool with a digital user interface that allows participants to explore the implications of applying circular economy strategies such as "Reduce" (for waste), Reuse (for materials), and Recovery (of energy though biogas generation) to the water urban cycle in different virtual catchments representing different settings. Several physical and online game-playing events took place where participants were able to take the appropriate measures to maximise Circular Economy for water when a virtual catchment was exposed to challenging scenarios, e.g., lower rainfalls and population growth. The players included students, environmental scientists, engineers, policy makers, and members of the public. The serious game was successfully used as a teaching tool in student classrooms (leading to an average improvement of about 26% in the number of correct answers). Furthermore, it made an effective debate facilitation tool contributing to the discussion of a multi-disciplinary expert panel by bringing new insights to the discussion. Finally, the Serious Game was used to organize the first e-sport competitive tournament between water professionals at an industry conference, paving the way for a novel form of engagement. This is a considerable contribution to public understanding at a time where the water industry struggles to sensitize a wider audience to the problems and reality of water in the context of climate change, growing resources scarcity, and environmental decline.